Reconstructing Criminal Policy on Asset Recovery: A Comparative Study of Anti-Corruption Enforcement in Indonesia and Nigeria: Merekonstruksi Kebijakan Pidana dalam Pemulihan Aset: Studi Perbandingan Penegakan Hukum Anti-Korupsi di Indonesia dan Nigeria - Ni Putu Ratnayutika (Universitas Muhammadiyah Sidoarjo, 2025)
General background: Corruption remains a systemic challenge that undermines governance, economic stability, and public trust, particularly in developing countries. Specific background: Indonesia and Nigeria have established legal frameworks for asset recovery, yet both continue to face structural, procedural, and institutional barriers that inhibit effective tracing, confiscation, and repatriation of illicit assets. Knowledge gap: Existing studies predominantly focus on normative analysis and provide limited comparative insights into how different legal systems influence the effectiveness of asset recovery. Aims: This study analyzes and compares the criminal policy frameworks of Indonesia and Nigeria to reconstruct an integrative and cross-jurisdictional model for asset recovery. Results: The study finds that Indonesia’s framework is normatively comprehensive but constrained by fragmented regulations and weak interagency coordination, while Nigeria shows stronger effectiveness through specialized institutions and non-conviction-based forfeiture despite challenges in political independence and bureaucratic integrity. Novelty: This research offers a comparative reconstruction that integrates legal norms, institutional performance, and international cooperation. Implications: The proposed model emphasizes the need for centralized asset-recovery bodies, expanded forfeiture mechanisms, and strengthened mutual legal assistance to enhance anti-corruption enforcement and restore public financial integrity. Highlights: Highlights contrasting effectiveness between Indonesia’s fragmented framework and Nigeria’s specialized institutions. Emphasizes the need for integrated national and international cooperation in asset recovery. Proposes a reconstructed policy model featuring centralized coordination and expanded forfeiture mechanisms. Keywords: Asset Recovery, Criminal Policy, Corruption, Indonesia, Nigeria